Effect of cochlear implant surgery on vestibular function: meta-analysis study - Iman Ibrahim; Sabrina Daniela da Silva; Bernard Segal; Anthony Zeitouni (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Importance Vestibular disorders have been reported following cochlear implant (CI) surgery, but the literature shows a wide discrepancy in the reported clinical impact. The aim of this meta-analysis is to quantify the effect of CI before and after surgery on the outcomes of vestibular tests, postural stability, and subjective perception of dizziness. Objective To evaluate the effects of CI surgery on vestibular function in adult patients (≥18 years) with sensorineural hearing loss who underwent unilateral or bilateral implantation. Data sources MEDLINE, PubMed, Web of Science and Cochrane Library from January 1, 1995, through July 12, 2016. Study selection Published studies of adult patients who received unilateral or bilateral CIs and whose vestibular function or postural stability was assessed before and after surgery. Data extraction From each study, test results before and after surgery were compared, for the following five tests: clinical head impulse test (HIT); bi-thermal caloric irrigation of the horizontal semicircular canal; vestibular evoked myogenic potential (VEMP); dizziness handicap inventory (DHI); and computerized dynamic posturography (CDP). Results Twenty-seven studies met all inclusion criteria. Most studies performed either bi-thermal caloric irrigation and/or VEMP, with fewer studies investigating changes in HIT, posturography or DHI. CI surgery significantly affected the results of caloric and VEMP testing. However, HIT results, posturography, and DHI, scores were not significantly affected after CI surgery. Conclusions and relevance CI surgery has a significant negative effect on the results of caloric as well as VEMP tests. No significant effect of CI surgery was detected in HIT, posturography, or DHI scores. Overall, the clinical effect of CI surgery on the vestibular function was found to be insignificant. Nonetheless, the potential effects of surgery on the vestibular system should be discussed with CI candidates before surgery.